2017
DOI: 10.15252/embr.201744661
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR ‐based gene drive in agriculture will face technical and governance challenges

Abstract: Comment on “Agricultural pest control with CRISPR‐based gene drive: time for public debate” by Courtier‐Orgogozo et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…Gutzmann et al argue that GD will face greater technical and governance challenges than suggested by our article. We agree with their points, although we did not develop these limitations in our paper.…”
mentioning
confidence: 62%
“…Gutzmann et al argue that GD will face greater technical and governance challenges than suggested by our article. We agree with their points, although we did not develop these limitations in our paper.…”
mentioning
confidence: 62%
“…Especially in the agricultural domain, governance debates follow patterns of polarization that are remarkably stable in the development from transgenic GMOs to CRISPR-edited crops and foods (Gutzmann et al, 2017;Macnaghten and Habets, 2020;Montenegro de Wit, 2020). For over 2 decades, a wide coalition of scientists, journalists, and industry actors has supported transgenic GMOs by highlighting increased technological control against biosafety concerns and by stressing the transformative potential of GMOs in addressing global challenges such as food security, malnutrition, and poverty in the Global South.…”
Section: Rethinking the Governance Of Crisprmentioning
confidence: 99%
“…The editing can be applied in engineering disease resistant transgenic plants but could also be used to engineer Asian citrus psyllids incapable of transmitting the bacterium responsible for HLB (Gutzmann et al, 2017). The editing can be applied in engineering disease resistant transgenic plants but could also be used to engineer Asian citrus psyllids incapable of transmitting the bacterium responsible for HLB (Gutzmann et al, 2017).…”
Section: A32 Control Of the Infectionmentioning
confidence: 99%